The impact of economic development on environmental sustainability - Duasa, Jarita (IIUM Press, 2009)
The study attempts to analyze the impact of income level, population growth on sustainable development indicators of 39 Muslim countries of the world. For this purpose, a GMM (Generalised Method of Moments) method of estimation is used to observe the impact based on cross-sectional data. The results indicate that the middle/higher income countries have less problem of air quality compared to low income countries which is at the higher process of industrialization. This is consistent with hypothesized relationship of environment Kuznets curve. It is also found that less population growth and low income countries contribute to better biodiversity or less percentage of counrty's territory in threatened ecoregions.